2022
DOI: 10.1007/s00784-022-04744-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral administration of Bifidobacterium animalis subsp. lactis HN019 on the treatment of plaque-induced generalized gingivitis

Abstract: Objectives This double-blind, randomized, placebo-controlled clinical trial evaluated the adjuvant effects of Bifidobacterium lactis HN019 on the treatment of plaque-induced generalized gingivitis. Materials and methods Sixty patients were submitted to professional supragingival scaling and prophylaxis. They were randomly assigned to test (probiotic lozenges containing B. lactis HN019, n = 30) or control (placebo lozenges, n = 30) groups. Lozenges were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Notably, in previous studies, measurements were based on gingival crevicular fluid (GCF) samples, which hampers comparison with our saliva-based data. Likewise, only a few studies investigated the impact of probiotics and gingivitis on cytokine levels; some found a favoring of the probiotics group [33][34][35], while others found no significant difference between the probiotics and placebo groups [36,37]. Our results support the latter finding, showing that supplementing with probiotics does not lead to significant increases or decreases in IL-1β, IL-8, or MCP-1 levels in individuals without clinical attachment loss.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Notably, in previous studies, measurements were based on gingival crevicular fluid (GCF) samples, which hampers comparison with our saliva-based data. Likewise, only a few studies investigated the impact of probiotics and gingivitis on cytokine levels; some found a favoring of the probiotics group [33][34][35], while others found no significant difference between the probiotics and placebo groups [36,37]. Our results support the latter finding, showing that supplementing with probiotics does not lead to significant increases or decreases in IL-1β, IL-8, or MCP-1 levels in individuals without clinical attachment loss.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, other previous gingivitis studies have shown that patients who return to gingival health after treatment continue to have inflammatory mediators in saliva for weeks after returning to healthy clinical conditions, indicating that longer interventions and follow-ups are needed to detect any changes [31,32]. Few studies have investigated the impact of experimental gingivitis or treatment on IL-1β, IL-8, or MCP-1 levels [33][34][35][36][37]. Notably, in previous studies, measurements were based on gingival crevicular fluid (GCF) samples, which hampers comparison with our saliva-based data.…”
Section: Discussionmentioning
confidence: 98%
“…The metaanalysis of 554 patients shows that oral probiotics did not lead to significant improvement in the GI, PI, and BOP values in the patients with plaque-induced gingivitis and microbiota 41 . However, some studies prove that the use of selected oral probiotics might promote additional clinical and immunological benefits while treating generalized gingivitis 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondary endpoints were changes in the Turesky modification of the Quigley and Hein Plaque Index (TQHPI) values after the one-month intervention period and after the one-month follow-up. The parameters were assessed as described in previous studies [ 59 , 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%